2021
DOI: 10.1016/j.psj.2021.101392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Akt activation on apoptosis-related gene expression in the crop tissues of male and female pigeons (Columba livia)

Abstract: The current study investigated whether the expression of apoptosis genes in the pigeon crops was affected by the Akt signaling pathway during crop milk formation. First, 78 pairs of adult White King pigeons were randomly assigned to 7 groups, and the expression of apoptosis-related genes and Akt signaling pathway-related proteins in the crop tissues during different breeding stages were examined. The results showed that the mRNA levels of Bak, caspase-3, caspase-6, and caspase-9 in female crops all increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…The membrane permeability of mitochondria is regulated by Bcl-2 family members, and the activation of initiator caspases and effector caspases is triggered sequentially. Caspase-3 and caspase-9 gene expression levels peaked at d 1 of chick rearing ( Xie et al, 2021 ). The mitochondria-dependent process possibly contributed to the desquamation to form pigeon milk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The membrane permeability of mitochondria is regulated by Bcl-2 family members, and the activation of initiator caspases and effector caspases is triggered sequentially. Caspase-3 and caspase-9 gene expression levels peaked at d 1 of chick rearing ( Xie et al, 2021 ). The mitochondria-dependent process possibly contributed to the desquamation to form pigeon milk.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression levels of various transporters and key synthetases of amino acids and fatty acids were commonly upregulated from the terminal phase of incubation to the early phase of chick rearing ( Xie et al, 2017 , 2020 ). Cell keratinization and mitochondria-dependent apoptosis seem to be indispensable factors that induce the degeneration of crop cells, and these nutritive epithelial cells are finally sloughed off into the cavity to form ‘milk’ ( Gillespie et al, 2013 ; Xie et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pigeons, lipids accumulation in crop tissue was enhanced during the process of milk formation. In addition, a previous study showed that the phosphorylation level of protein kinase B (Akt) was inhibited at the peak of lactation (Xie et al, 2021). INSR/PI3K (phosphatidylin‐ositol‐3‐kinase)/Akt is one of the classical pathways in response to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that insulin can bind to insulin receptors, and that phosphorylated insulin receptor substrate 1 ( IRS1 ) regulates protein synthesis in skeletal muscle satellite cells and in the breast tissue of dairy cows by activating signaling pathways such as protein kinase B-target of rapamycin complex 1 ( Akt-TORC1 ; Bolster et al, 2004 ; Yang et al, 2015 ; Xie et al, 2021 ; Ye et al, 2022 ). Our previous study showed that the serum prolactin and insulin contents in lactating pigeons were significantly higher than those in nonbreeding pigeons, and the phosphorylated protein levels of IRS1, Akt, TOR, ribosomal protein S6 kinase 1 ( S6K1 ), ribosomal protein S6 ( S6 ), eukaryotic initiation factor 4E binding protein 1 ( 4EBP1 ), and eukaryotic initiation factor 4E ( eIF4E ) were all upregulated during lactation ( Hu et al, 2016 ).…”
Section: Hormonal Changes and Signaling Pathways Involved In Pigeon C...mentioning
confidence: 99%